Studi Komparatif Hukum Kepemilikan Tanah Antara Indonesia dan Malaysia - Handar Subhandi Bakhtiar; Atik Winanti; Pradipta Prihantono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Land Ownership in Indonesia, is regulated in Article 5 of the Basic Agrarian Law (UUPA) No. 5 of 1960. UUPA regulates various types of land rights in Indonesia, such as ownership rights, lease rights, use rights, and business use rights. This regulation aims to distribute natural resources, ensure legal certainty over land, and protect the rights of communities affected by land use policies. Meanwhile, Malaysia has a land ownership legal system influenced by British law due to its colonial period. In this context, land law in Malaysia is regulated by various laws, including the National Land Code (NLC) 1965, which regulates land rights, land registration, and land-related rights. In Malaysia, land is divided into several categories of rights, such as freehold and leasehold. The land registration system in Malaysia is more centralized, and land regulations are also implemented through state institutions. Unlike Indonesia, which prioritizes customary rights in land management, Malaysia tends to prioritize national land regulation and administration through a more modern and structured system.